Kewenangan Pemerintah Daerah Di Bidang Pertanahan - Dady Hendrawan; Hendrich Juk Abeth; Ayu Syaputri (Collegium Studiosum Journal, 2018)
In Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia it is stated that; "The water and natural resources contained therein shall be controlled by the State and used as much as possible for the prosperity of the people". This article clearly regulates the relationship between the State and, land, earth, water and natural resources contained therein are controlled by the State, with the aim of the welfare of its people. Thus, the task of the State of Indonesia is not merely to provide legal protection, legal certainty and besides that there is a more fundamental task, namely to utilize all land and natural resources contained therein for the greatest prosperity of the people. The birth of Law No. 5 of 1960 concerning Agrarian Principles (hereinafter referred to as UUPA) is an instrument to create prosperity and justice for all spilled Indonesians. This law was born to abolish all laws and regulations which for nearly 350 years had carried out massive exploitation of the land and natural resources contained therein.